Surfactant protein D is a biomarker of influenza‐related pediatric lung injury. Issue 2 (7th December 2021) - Chakrabarti, Arindam; Nguyen, Allen; Newhams, Margaret M.; Ohlson, Maikke B.; Yang, Xiaoying; Ulufatu, Sheila; Liu, Shannon; Park, Summer; Xu, Min; Jiang, Jenny; Halpern, Wendy G.; Anania, Veronica G.; et al.
Abstract: Background: Biomarkers that can risk‐stratify children with influenza virus lower respiratory infection may identify patients for targeted intervention. Early elevation of alveolar‐related proteins in the bloodstream in these patients could indicate more severe lung damage portending worse outcomes. Methods: We used a mouse model of human influenza infection and evaluated relationships between lung pathophysiology and surfactant protein D (SP‐D), SP‐A, and Club cell protein 16 (CC16). We then measured SP‐A, SP‐D, and CC16 levels in plasma samples from 94 children with influenza‐associated acute respiratory failure (PICFLU cohort), excluding children with underlying conditions explaining disease severity. We tested for associations between levels of circulating proteins and disease severity including the diagnosis of acute respiratory distress syndrome (ARDS), mechanical ventilator, intensive care unit and hospital days, and hospital mortality. Results: Circulating SP‐D showed a greater increase than SP‐A and CC16 in mice with increased alveolar‐vascular permeability following influenza infection. In the PICFLU cohort, SP‐D was associated with moderate‐severe ARDS diagnosis ( p = 0.01) and with mechanical ventilator ( r = 0.45, p = 0.002), ICU ( r = 0.44, p = 0.002), and hospital days ( r = 0.37, p = 0.001) in influenza‐infected children without bacterial coinfection. Levels of SP‐D were lower in children with secondary bacterial pneumonia ( p = 0.01) and not associated with outcomes. CC16 and SP‐A levels did not differ with bacterial coinfection and were not consistently associated with severe outcomes. Conclusions: SP‐D has potential as an early circulating biomarker reflecting a degree of lung damage caused directly by influenza virus infection in children. Secondary bacterial pneumonia alters SP‐D biomarker performance.